2022
DOI: 10.3390/genes13010108
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phosphorus Stress Related Proteins in the Seedlings of Dongxiang Wild Rice (Oryza Rufipogon Griff.) Using Label-Free Quantitative Proteomic Analysis

Abstract: Phosphorus (P) deficiency tolerance in rice is a complex character controlled by polygenes. Through proteomics analysis, we could find more low P tolerance related proteins in unique P-deficiency tolerance germplasm Dongxiang wild rice (Oryza Rufipogon, DXWR), which will provide the basis for the research of its regulation mechanism. In this study, a proteomic approach as well as joint analysis with transcriptome data were conducted to identify potential unique low P response genes in DXWR during seedlings. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
2
1
0
Order By: Relevance
“…Our results indicate that roots play a more critical role in Pi starvation than leaves. Our findings agree with Li et al (2010) and Deng et al (2022), where Dongxiang and Lagrue rice varieties upregulated the expression of Pi transporters OsPTs and acid phosphatase OsPAPs in roots. The upregulation of the OsPTs gene is responsible for Pi acquisition from the soil and mobilization of Pi within plants (Shin et al, 2004).…”
Section: Molecular Response To Low Phosphate Conditionssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results indicate that roots play a more critical role in Pi starvation than leaves. Our findings agree with Li et al (2010) and Deng et al (2022), where Dongxiang and Lagrue rice varieties upregulated the expression of Pi transporters OsPTs and acid phosphatase OsPAPs in roots. The upregulation of the OsPTs gene is responsible for Pi acquisition from the soil and mobilization of Pi within plants (Shin et al, 2004).…”
Section: Molecular Response To Low Phosphate Conditionssupporting
confidence: 91%
“…The six selected genes were involved in low-Pi-responsive pathways. The increase in their expression under low Pi conditions has also been reported in other studies (Zhou et al, 2008;Li et al, 2010;Deng et al, 2022). Significantly, the OsPAP21 gene expression increased approximately 140 times in plants grown in the P+113 medium compared to those grown in the P0 medium.…”
Section: Molecular Response To Low Phosphate Conditionssupporting
confidence: 84%
“…Two of these genes, LOC Os12g09620 and LOC Os03g40670, were found to be present at both the transcriptome and proteome levels. The thorough investigation revealed that in dealing with low P stress condition, DXWR employs various strategies which include enhancing the the expression of PAPs, modifying membrane location of P transporters, rhizosphere area, and AS, and decreasing ROS activity [68]. This research will provide some light on the molecular mechanisms underlying low P resistance in DXWR and enable cloning of the P-deficit tolerance genes from wild rice.…”
Section: New Insights For Plant Phosphate Starvation Response At the ...mentioning
confidence: 98%